Resting-state MEG of whole-brain functional network in cingulate gyrus epilepsy - Leng, Xuerong; Yang, Xue; Xiang, Jing; Wang, Rui; Dong, Haoran (Frontiers in Neurology, 2026)
ObjectiveTo investigate the connectivity and formation mechanism of the whole brain resting-state network in cingulate gyrus epilepsy and to identify biological markers and potential neuromodulation targets for this condition.MethodsFifteen patients with cingulate gyrus epilepsy and 15 healthy controls underwent resting-state magnetoencephalography (MEG). To compute functional network connectivity at the source level, we used MEG Processor software. Twenty regions of interest (ROI) were selected from both cerebral hemispheres, and connectivity was assessed across four frequency bands: theta (4–7.5 Hz), alpha (8–13 Hz), beta (14–30 Hz), and gamma (31–80 Hz).ResultsThe number of neocortical-related functional connectivity differences increased with the frequency band, being smallest in the theta (θ) band and largest in the gamma (γ) band. The connections between the angular gyrus (AG) and the occipital gyrus (OG) and between the OG and the superior temporal gyrus (STG) were the most influential in terms of functional connectivity within the neocortex. The connectivity between the anterior cingulate cortex (ACC) and the inferior frontal gyrus (IFG) showed the most pronounced differences in the α, β, and γ bands. Among the functional connectivities to the posterior cingulate gyrus (PCC), those involving the AG-PCC and STG-PCC were the most significant. The hippocampal-related functional connectivity differed from neocortex-related functional connectivity, and the number of differential functional connections was greater in the θ-band than in the α-band.ConclusionEnhanced functional connectivity (AG-OG and OG-STG) of the neocortical surface may be characteristic features of the resting-state network in cingulate gyrus epilepsy and could serve as potential biological markers for this condition. The IFG’s close relationship with the ACC suggests it may be a candidate target for neuromodulation therapy in anterior cingulate gyrus epilepsy. Similarly, the AG and STG’s connections with the PCC make them potential candidates for neuromodulation therapy in posterior cingulate gyrus epilepsy for future investigation.